Feeling like different persons: Becoming English teachers through overseas teaching internships - Isna Agustin; Nurfitri Longdaeva; Elok Putri Nimasari; Ana Maghfiroh (Universitas Islam Negeri Ar-Raniry, 2026)
This study examines the professional identity development of Indonesian pre-service English teachers during a short-term international teaching internship in Southern Thailand, specifically exploring how participants perceived themselves as becoming